USING VIDEO ON YOUTUBE TO IMPROVE STUDENTS’ GRAMMAR ABILITY - Resti Citra Dewi; Supriadi -; Fitria Hardini (Journal of Language, Literature and Teaching, 2022)
The rapid development of technology has had an impact on the field of education. In this case, an educator must be able to be more creative and innovative to build and stimulate students' interest to learn in the classroom while teaching learning process. One of the positive things from the impact of technological developments to support the teaching and learning process is the use of technology-based learning media such as making interesting videos and uploading them to YouTube. YouTube videos can be repeated and can be accessed anywhere if the device and internet network support. YouTube videos were used in this study as a learning media to improve students’ grammar ability. The sudents in this study are the first semester majoring accounting at Institut Teknologi dan Bisnis Indonesia. The total number of students in this Classroom Action Research (CAR) is 30 students. After taking two cycles of action, it can be concluded that the use of videos that are made as attractive as possible and uploaded to YouTube as a learning media to improve students' grammar ability is effective in the teaching and learning process, besides that YouTube is also universal, can be viewed repeatedly, and can enhance the creativity of an educator.